Azolla cover significantly decreased CH4 but not N2O emissions from flooding rice paddy to atmosphere. Issue 1 (2nd January 2018) - Kimani, Samuel Munyaka; Cheng, Weiguo; Kanno, Takamori; Nguyen-Sy, Toan; Abe, Ryoko; Oo, Aung Zaw; Tawaraya, Keitaro; Sudo, Shigeto
ABSTRACT: Azolla ( Azolla filiculoides ) is a common aquatic fern that has been used successfully as a dual crop with lowland rice. It grows rapidly and has the ability to fix N2 for rice paddy. However, its ecological significance especially on greenhouse gases emissions remains unclear. To investigate the effect of azolla cover on methane (CH4 ) and nitrous oxide (N2 O) emissions from rice paddy, a pot experiment with two treatments, control (rice plant only) and azolla cover (rice plus azolla covering on the flooding water), was carried out in Tsuruoka, Yamagata, Japan, in 2016. The results showed that the rice growth parameters, like shoot height, maximum and productive tiller numbers, and plant biomass were not significantly different between the two treatments. Dual cropping of azolla with rice significantly suppressed CH4 emissions, likely due to an increase in dissolved oxygen concentration and redox potential at the soil-water interface between flooding water and soil surface. There were significant ( P <  0.05) positive correlations between CH4 flux and night respiration (CO2 emissions) between the two treatments. The cumulated CH4 emissions during the growth period until 106 days after transplanting (DAT) was significantly lower at 36.2 g C m −2 from azolla cover treatment than that from control treatment pot at 55.4 g C m −2 . A prolonged nonsignificant N2 O emission under the azolla cover treatment after the initial highest peak at 15 DAT was recorded due to denitrification of the nitrate in initial soil. No further N2 O emissions were recorded thereafter from both treatments. Azolla cover did not affect N2 O emissions from both treatments.